Effect of air-gap on response of fabricated slim floor beams in fire. (10th June 2019) - Alam, Naveed; Nadjai, Ali; Maraveas, Chrysanthos; Tsarvdaridis, Konstantinos; Kahanji, Charles
Abstract : Purpose: The purpose of this study is to investigate the effect of the airgap on thermal behaviour and structural response of fabricated slim floor beams (FSFBs) in fire. Design/methodology/approach: A detailed analytical model is established and validated by replicating the response of FSFBs. The validated finite element modelling method is then used to perform sensitivity analysis. First, the influence of the airgap presence is analysed, and later, the effect of the airgap size on thermal behaviour and structural response of FSFBs at elevated temperatures is investigated. Findings: Results from the study demonstrate that the presence of the airgap has a considerable influence on their thermal behaviour and structural response of FSFBs. The size of the airgap, however, has no significant influence on their thermal and structural response in fire. Originality/value: No investigations, experimental or analytical, are available in literature addressing the effect of airgap on the structural response of FSFBs in fire. The presence of airgap is helpful and beneficial; hence, the findings of this research can be used to develop designs for structural members with airgap as an efficient and inexpensive way to improve their response in fire.